The Influence of the Deep Learning Approach in Pancasila Education Learning on Improving Students' Critical and Creative Thinking Skills - Sulpadli; Budi Mulyono (Thinking Skills and Creativity Journal, 2026)
Students’ critical and creative thinking skills remain a challenge in twenty first century learning because instructional processes have not yet fully optimized the development of higher order thinking skills. This study aimed to examine the effect of the deep learning approach in Pancasila Education learning on improving students’ critical and creative thinking skills. This research employed a quantitative approach using a quasi experimental method with a nonrandomized control group pretest-posttest design. The research subjects consisted of 72 eleventh grade students who were divided into an experimental group and a control group. Data were collected using critical and creative thinking skills tests that had met the criteria of validity, reliability, difficulty level, and discrimination index. Data analysis was conducted using descriptive statistics, the Shapiro Wilk normality test, and hypothesis testing using the Wilcoxon and Mann Whitney U tests. The results showed that the deep learning approach had a significant effect on improving students’ critical and creative thinking skills compared with conventional learning and was able to develop both skills simultaneously. The study concludes that the deep learning approach is effective for implementation in Pancasila Education learning to foster students’ higher order thinking skills. The implication of this study emphasizes that the application of the deep learning approach can serve as an innovative instructional strategy that promotes student centered, meaningful, reflective learning and aligns with the demands of twenty first century competencies.